2014
DOI: 10.1073/pnas.1315778111
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature hyperpolarization of nuclear spins in bulk

Abstract: Dynamic nuclear polarization (DNP), a means of transferring spin polarization from electrons to nuclei, can enhance the nuclear spin polarization (hence the NMR sensitivity) in bulk materials at most 660 times for 1 H spins, using electron spins in thermal equilibrium as polarizing agents. By using electron spins in photo-excited triplet states instead, DNP can overcome the above limit. We demonstrate a 1 H spin polarization of 34%, which gives an enhancement factor of 250,000 in 0.40 T, while maintaining a bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
167
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(169 citation statements)
references
References 41 publications
0
167
2
Order By: Relevance
“…The development of a general nuclear hyperpolarization technique at arbitrary fields would enable measurements of biomolecules and reaction dynamics that were not accessible by the present techniques while decreasing routine NMR measurement times by orders of magnitude [1]. Several approaches to dynamic nuclear polarization (DNP) processes have been demonstrated that enhance nuclear spin polarization; however, the majority are limited to specific fields [2][3][4][5], low temperatures [6,7], specific molecules [8], or require microwave irradiation of the sample [8,9]. Low temperature is particularly problematic for liquid-state biological samples, where freezing leads to a loss of spectral resolution [10].…”
Section: Introductionmentioning
confidence: 99%
“…The development of a general nuclear hyperpolarization technique at arbitrary fields would enable measurements of biomolecules and reaction dynamics that were not accessible by the present techniques while decreasing routine NMR measurement times by orders of magnitude [1]. Several approaches to dynamic nuclear polarization (DNP) processes have been demonstrated that enhance nuclear spin polarization; however, the majority are limited to specific fields [2][3][4][5], low temperatures [6,7], specific molecules [8], or require microwave irradiation of the sample [8,9]. Low temperature is particularly problematic for liquid-state biological samples, where freezing leads to a loss of spectral resolution [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Tateishi and his collaborators reported that they successfully suppressed the nuclear spin relaxation at room temperature by (partially) deuterating p-terphenyl and pentacene [60]. They replaced 4 of the 14 hydrogen atoms in a p-terphenyl (p-terphenyl-…”
Section: Progress In Triplet-dnp Target Developmentmentioning
confidence: 99%
“…NOVEL was soon replaced by ISE which gives a much higher efficiency due to the adiabatic sweep of the magnetic field. 34,[38][39][40] Note that both of these samples were especially chosen to demonstrate the NOVEL or ISE effect. Thus, one of our goals in the results reported here was to investigate the potential of the NOVEL sequence in samples used in current applications of DNP in NMR, i.e., samples doped with a few tens of mM of stable free radicals such as the narrow-line species 1,3-bisdiphenylene-2-phenylallyl (BDPA) or nitroxides, both of which are used in contemporary CW DNP experiments.…”
Section: Introductionmentioning
confidence: 99%